Building Java programs a back to basics approach - Reges, Stuart (Pearson Education Limited, 2014)
Building Java Programs: A Back to Basics Approach, Third Edition, introduces novice programmers to basic constructs and common pitfalls by emphasizing the essentials of procedural programming, problem solving, and algorithmic reasoning. By using objects early to solve interesting problems and defining objects later in the course, Building Java Programs develops programming knowledge for a broad audience.